Impact of Different Metabolic Indicators on Ventricular Repolarization Indices in Obese Children: A Case Control Study - Asmaa A El Sehmawy; Rasha Abd El Samad Fawaz; Nadia Ahmed Agiba; Eman Aziz Elsherbiny; Nglaa Fathi Agaba; Doaa Sayed Mohammed; Haidy Mahmoud Nasr; Fatma Elzhraa AE Diab; Amal M Ahmed; Shorouk Issa Mahfouz; Heba T Okda; Doaa Sadek Ahmed (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Obesity, insulin resistance, and dyslipidemia may impact ventricular repolarization in children. Objectives: The study aimed to identify the relationship between various metabolic indicators and ventricular repolarization indices among obese children compared to healthy ones. Methods: A case-control study included 90 children, divided into two groups: 45 obese children (cases) and 45 children with normal weight (controls). Electrocardiogram (ECG) readings were analyzed to calculate several parameters, including corrected QT (QTc), QTc dispersion (QTcd), JTc dispersion, and the TpTe interval, using 12-lead surface ECGs. Both groups were also assessed for lipid profiles, fasting plasma glucose (FPG), and serum insulin to calculate the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Results: Obese children had significantly higher serum levels of triglycerides, cholesterol, LDL, fasting insulin, and HOMA-IR compared to controls. Also, they significantly had longer mean values of QTcd and JTcd with no significant difference in TpTe interval between both groups. A significant positive correlation was detected between QTc and JTc dispersion and the following variables: waist circumference, body mass index (BMI), blood pressure, fasting insulin, HOMA-IR index, and LDL. Additionally, no significant difference was revealed between obese children with and without metabolic syndrome regarding ventricular repolarization ECG parameters. Conclusion: Greater JTc dispersion (ms) and QTc dispersion (ms) were observed in obese children with a positive correlation to waist circumference, BMI, and insulin resistance.